Esthetic Management of Maxillary Anteriors with Complicated and Uncomplicated Fractures Using Different Fragment Reattachment Approaches - A, Lavanya; Tewari, Rajendra Kumar; Alam, Sharique (Journal of Dentistry Indonesia, 2024)
Appropriate management of anterior tooth fracture restores the function and aesthetics and provides a positive psychological impact for the patient. One of the most conservative approaches for such a restoration is reattachment; if a fracture fragment remains attached to the tooth and is available, as in young patients, immediate reporting helps preserve the vitality and long-term defense mechanism. Objective: This case report provides two cases with varied approaches for the management of complicated and uncomplicated crown fractures using reattachment procedures. Case report: During the clinical examination, the first case described the management of an uncomplicated fracture using the putty index technique. The second case report describes the management of a complicated fracture of the upper central incisor, which invades the biological width using flap elevation and fiber post-cementation. Conclusion: Fragment reattachment is a reliable, conservative, and immediate alternative technique having better retentive and aesthetic values. Tooth fragment reattachment provides dentists with a conservative approach for an aesthetically satisfactory tooth reconstruction.